A new species of Asterocheres (Copepoda, Siphonostomatoida, Asterocheridae) associated to Placospongia cristata Boury-Esnault (Porifera) in Bahia State, Brazil - Bispo, Ricardo; Johnsson, Rodrigo; Neves, Elizabeth (Zootaxa, 2006)
The siphonostomatoid fauna associated with the sponge, Placospongia cristata Boury-Esnault, is studied for the first time. Asterocheres bimbarrensis n. sp. is characterized by having two spines distally on the third endopod of P4 instead of a seta and a spine, is described and compared with its congeners. Another species of the genus, A. neptunei Johnsson, is also found associated with this sponge, however, P. cristata may not be its main host since it is scarce. Asterocheres neptunei has previously been recorded associated with an undetermined sponge in the southeast region of Brazil thus the present record extends its distribution to the northeast. This study is the first record of the sponge P. cristata in Bahia.